PDS (proportional derivative and strain) feedback control of a flexible structure with closed-loop mechanism - Matsuno, F.; Ohno, T.; Orlov, Y.V. (Proceedings of the 38th IEEE Conference on Decision and Control (Cat. No.99CH36304), 1999)
A simple Space truss structure, a rigid connection of two flexible beams, is modeled as a distributed parameter system subject to geometric constraints. An output PDS feedback control synthesis is developed for this structure. The synthesis is carried out in the infinite-dimensional setting yielding a stabilizing control algorithm. Due to simplicity of implementation, the algorithm becomes extremely attractive under limitations on the computer power in the space. The effectiveness of the control strategy proposed is supported by experimental tests.